2014
DOI: 10.1038/onc.2014.36
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear SIPA1 activates integrin β1 promoter and promotes invasion of breast cancer cells

Abstract: SIPA1 (signal-induced proliferation-associated protein 1) is a GTPase activation protein that can catalyze the hydrolysis of Rap1 bound GTP to GDP. Recently attention has been paid to a potential role for SIPA1 in cancer metastasis; however, the underlying mechanism of how changes in SIPA1 levels may lead to increased metastasis remains poorly understood. In this study, we showed that SIPA1 was mainly localized to the nuclei in highly invasive breast cancer tumor tissue and MDA-MB-231 cells. Knockdown of SIPA1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
42
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 58 publications
(66 reference statements)
3
42
1
Order By: Relevance
“…Previous studies have suggested that SIPA-1 is involved in certain types of cancer activity, including mutation (23,24), apoptosis (12,25), proliferation (4,15), invasion (15,16) and metastasis (13,26,27). In the present study, it was observed that SIPA-1 additionally regulates bladder cancer cell metastasis and invasion (Figs.…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Previous studies have suggested that SIPA-1 is involved in certain types of cancer activity, including mutation (23,24), apoptosis (12,25), proliferation (4,15), invasion (15,16) and metastasis (13,26,27). In the present study, it was observed that SIPA-1 additionally regulates bladder cancer cell metastasis and invasion (Figs.…”
Section: Discussionsupporting
confidence: 64%
“…Recent studies have indicated that SIPA-1 is associated with the motility of cancer cells (14)(15)(16). In addition, nuclear SIPA-1 activates the integrin β1 promoter and promotes the invasion of breast cancer cells (15). SIPA-1 serves a variety of functions during disease progression and exerts contrasting effects on growth and motility of colorectal cancer cells (13).…”
Section: Introductionmentioning
confidence: 99%
“…SIPA1 (Takahara et al ., 2017; Zhang et al ., 2017) and RAB3D (Yang et al ., 2003; Zhang et al ., 2015) are both involved in proliferation, invasion, and metastasis in multiple cancers, exhibiting similar functions to APE1. All four genes showing significantly reduced expression in a dose‐dependent manner (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…A majority of studies showed that rare GCH1 coding variants were considered as a risk factor for Parkinson's disease Hjermind et al, 2006;Cobb et al, 2009;Mencacci et al, 2014]. Moreover, previous studies have focused on the association of SIPA1 with carcinogenesis of many cancers, such as breast cancer, lung cancer, colorectal cancer, cervical cancer and so on [Minato and Hattori, 2009;Brooks et al, 2010;Ji et al, 2012;Xie et al, 2013;Zhang et al, 2015]. Therefore, the role of these genes (VPS13C, MIR4697, GCH1, and SIPA1L2) awaits discovery in the pathophysiologic pathway of PD.…”
Section: Discussionmentioning
confidence: 98%